2015
DOI: 10.1021/acs.jpcc.5b04399
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ag Dopant Atoms in CdSe Nanocrystals by Reverse Monte Carlo Analysis of EXAFS Spectra

Abstract: The structure of CdSe nanocrystals doped with 0.2%–2.5% Ag corresponding to 1.1–13.6 Ag atoms per nanocrystal is studied in detail by a combination of X-ray diffraction (XRD) and X-ray absorption spectroscopy at the Ag–K, Cd–K, and Se–K edges. X-ray absorption near-edge structure (XANES) data are compared with ab initio multiple scattering simulations. Extended X-ray absorption fine structure (EXAFS) spectra are analyzed by reverse Monte Carlo (RMC) simulations. The XANES data provide evidence that Ag is locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…Timeframes of such a simulated reaction at a single‐dot level are shown in Figure d–g . More recently reported extended x‐ray absorption fine structure studies confirmed that Ag ions are located inside the CdSe CQDs and occupy interstitial sites for doping concentrations below 2.5 % …”
Section: Doping Schemesmentioning
confidence: 84%
See 1 more Smart Citation
“…Timeframes of such a simulated reaction at a single‐dot level are shown in Figure d–g . More recently reported extended x‐ray absorption fine structure studies confirmed that Ag ions are located inside the CdSe CQDs and occupy interstitial sites for doping concentrations below 2.5 % …”
Section: Doping Schemesmentioning
confidence: 84%
“…[56] More recently reported extended x-ray absorption fine structure studies confirmed that Ag ions are located inside the CdSe CQDs and occupy interstitial sites for doping concentrations below 2.5 %. [118] InAs CQDs have also been dopedw ith aliovalent cation, such as Cd 2 + , [119] Cu + ,A u 3 + ,a nd Ag + . [57,120] Geyer et al [119] reported that the conductivity of InAs nanocrystal solids changed from n-type to p-type upon doping the nanocrystals with Cd.…”
Section: Doping Through Aliovalent Impuritiesmentioning
confidence: 99%
“…To circumvent this problem, one may run a series of RMC-EXAFS simulations using different starting models, choosing as the final solution the optimized structure model that resulted in the best agreement with experimental data (28). For example, in a recent study by Kompch et al (29), such an approach was used for RMC-EXAFS studies of localization of Ag dopant atoms in CdSe nanocrystals.…”
Section: Reverse Monte Carlo Modeling Of Nanoparticle Structurementioning
confidence: 99%
“…To summarize, atomic-scale simulation of nanomaterial structure, guided by XAS data, is a new and rapidly developing field. The importance of and growing interest in such studies are supported by a number of recent publications devoted to this topic (15,17,19,26,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The approaches described in these articles often rely on similar ideas, but their implementation varies because such combined studies are still a relatively new tool for modeling NP structure.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the PL intensity changes seen across dopant levels are intimately associated with a charging event due to the introduction of anions and cations to the NCs. Considering the significant evidence that the Ag + impurity ions are introduced interstitially with eventual conversion to substitutional dopants 25,48,49 and the lack of a trend in the charge with respect to the dopant amount, the PL intensity changes are likely not exclusively due to the internal dopants. Further evidence for this hypothesis comes from the Page 9 of 20 Nano Letters 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 control doping samples, which showed a clear enhancement in the exciton PL intensity upon introduction of the other cations that do not necessarily dope the NC lattice (Figure 3d).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%